SANATORIUM VOUCHER AS A PRIMARY ACCOUNT DOCUMENT - Tatyana Ivanovna Kisilevich (Science and Innovation Center Publishing House, 2019)
Purpose. The goal is to study the organization of the correct document flow of spa-resort vouchers taking into account the introduction of strict reporting forms as a payment document and the validity of the application of value-added tax exemption.